Analisis Evaluatif Moderasi Beragama: Tantangan Tata Kelola, Dilema Wacana, dan Rekomendasi Penguatan Kebijakan - Fihrisi, Fathan; Suwardi, Suwardi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The Religious Moderation Program is a key policy of the Indonesian government, mainstreamed through the National Medium-Term Development Plan (RPJMN) 2020–2024. This program aims to foster attitudes of balance, tolerance, and the prevention of extremism in order to reduce religion-based conflicts. However, the implementation of this program often faces substantive challenges, marked by social tensions and criticism that the policy remains largely rhetorical and top-down, lacking genuine effectiveness at the grassroots level. This study aims to objectively analyze the factors contributing to this gap and to formulate constructive recommendations for improving policy governance. The research employs a qualitative descriptive method based on literature study, reviewing reputable academic journals through the theoretical framework of policy implementation by Mazmanian and Sabatier, as well as Norman Fairclough’s Critical Discourse Analysis (CDA). The evaluation results reveal three main areas that hinder the program’s impact: 1) Managerial Governance Challenges, where the top-down approach, dualism of programs (the Religious Moderation Village Program and the Religious Harmony-Conscious Village Program), and limited public participation constrain operational effectiveness, as analyzed through the Mazmanian–Sabatier framework. 2) Discourse Communication Dilemmas, where the policy texts are prone to interpretation (through CDA) as carrying hidden ideological agendas that potentially marginalize conservative religious views, thus triggering ideological resistance that requires careful management. 3) Lack of a Holistic Policy Priority, referring to the tendency to overemphasize “harmony” while failing to prioritize Freedom of Religion and Belief (FORB) as a central agenda. This study recommends adaptive governance reform, strengthened inter-agency coordination, and the reaffirmation of Religious Moderation as a constitutional guarantee of Freedom of Religion and Belief, to ensure a more sustainable and inclusive impact.